RIPK2 as a New Therapeutic Target in Inflammatory Bowel Diseases - Honjo, Hajime; Watanabe, Tomohiro; Kamata, Ken; Minaga, Kosuke; Kudo, Masatoshi (Frontiers in Pharmacology, 2021)
IInflammatory bowel diseases (IBDs) are becoming more frequent worldwide. A significant fraction of patients with IBD are refractory to various types of therapeutic biologics and small molecules. Therefore, identification of novel therapeutic targets in IBD is required. Receptor-interacting serine/threonine kinase 2 (RIPK2), also known as receptor-interacting protein 2 (RIP2), is a downstream signaling molecule for nucleotide-binding oligomerization domain 1 (NOD1), NOD2, and Toll-like receptors (TLRs). RIPK2 is expressed in antigen-presenting cells, such as dendritic cells and macrophages. Recognition of microbe-associated molecular patterns by NOD1, NOD2, and TLRs leads to the interaction between RIPK2 and these innate immune receptors, followed by the release of pro-inflammatory cytokines such as TNF-alphaIL-6, and IL-12/23p40 through the activation of nuclear factor kappa B and mitogen-activated protein kinases. Thus, activation of RIPK2 plays a critical role in host defense against microbial infections. Recent experimental and clinical studies have provided evidence that activation of RIPK2 is involved in the development of autoimmune diseases, especially IBDs. In addition, the colonic mucosa of patients with IBD exhibits enhanced expression of RIPK2 and associated signaling molecules. Furthermore, the blockage of RIPK2 activation ameliorates the development of experimental murine colitis. Thus, activation of RIPK2 underlies IBD immunopathogenesis. In this review, we attempt to clarify the roles played by RIPK2 in the development of IBD by focusing on its associated signaling pathways. We also discuss the possibility of using RIPK2 as a new therapeutic target in IBD.